Methodologies of Change in the Contemporary Islamic World: 12-14 Sha'ban 1414/24-26 January 1994 Kuwait City, Kuwait (American Journal of Islam and Society, 1994)
llris seminar was the second in a series of seminars held jointly bythe International Institute of Islamic Thought (IIIT) in cooperation withthe Kuwaiti Department of Awqaf. The inaugural session of the seminarwas addressed by the Minister for Awqaf and Islamic Affairs, Jam'an al'Azimi, who stated that the topic of the seminar sufficed to indicate itsimportance. The following speaker, the Secretary of the Ministry, Khalidal Zir, underlined the fact that while everyone agreed on the need to returnto the pristine teachings of the Qur'an and the Sunnah, it was not aneasy matter to determine how, in practical tenns, this might be achieved.This is why, the Secretary said, this seminar was convened.Taha Jabir al 'Alwani, President of the International Institute ofIslamic Thought, after making his opening remarks, delivered a paperentitled The Horizons of Change and Its Approaches, in which he statedthat the Arab world had very recently reached a critical stage. Manyanalytical studies of various aspects of the Arab situation, he added, hadbeen conducted from several different perspectives. Undoubtedly, on thebasis of these studies, the outlines of an alternative civilizational projectmay emerge. It is for this reason that the topic of the seminar, "Methodologiesof Change in the Contemporary Islamic World," is of such overwhelmingimportance.Muhammad al Ghazali, the noted Muslim 'alim and author, thenspoke on behalf of the seminar participants. Prefacing his remarks bynoting the importance of Kuwait in the Arab and Muslim worlds, alGhazali explained that it is the duty of Muslims everywhere to work togetherto further the cause of Islam. This is why, he added, the cooperationof the Kuwaiti Ministry with the International Institute of IslamicThought was such a commendable undertaking.The seminar was comprised of four distinctive themes. The first onedealt with defining the concept of change within the Islamic paradigm,beginning with the Qur'an, the Sunnah, and the historical experience ofIslam. This concept may be studied in light of the theories and opinionsof the classical scholars of Islam. In addition, it may prove beneficial tostudy it in conjunction with such similar concepts within the Islamic paradigmas tajdid, reform, revival, awakening, revolution, modernization,development, and progress. Topics for discussion included the following: ...